2016
DOI: 10.4067/s0717-95022016000200035
|View full text |Cite
|
Sign up to set email alerts
|

Biological Maturity Status and Motor Performance in Fourteen-Year-old Basketball Players

Abstract: SUMMARY:The aims of this study were to detect biological maturity and certain athletic skills in boys aged 14 participating in competitive basketball, and to compare certain athletic skills of participants according to their biological maturity status. The participants were most talented Serbian basketball players (n= 49) who were divided into three groups according to their maturity status: early (n= 14), average (n= 24) and late maturing (n= 11). Biological maturity status of participants was assessed by tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…Although we were unable to find a citation with reference to basketball players, we contend that it is a very important issue because biological maturation varies considerably among youth sport players of the same chronological age, with those with advanced maturity status outperforming their less mature peers [7,10]. The present study shows that early maturing players are taller and heavier, results that are consistent with previous research [14][15][16][17]. However, at the physical and technical level, available data is less consistent.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although we were unable to find a citation with reference to basketball players, we contend that it is a very important issue because biological maturation varies considerably among youth sport players of the same chronological age, with those with advanced maturity status outperforming their less mature peers [7,10]. The present study shows that early maturing players are taller and heavier, results that are consistent with previous research [14][15][16][17]. However, at the physical and technical level, available data is less consistent.…”
Section: Discussionsupporting
confidence: 90%
“…However, at the physical and technical level, available data is less consistent. For example, Jakovljević et al [17] reported that average maturing basketball players outperformed early and late maturers, whereas Coelho e Silva et al [18] and Leonardi et al [19] concluded that physical performance and technical skills were independent of a player's maturity status, for boys and girls, respectively. On the other hand, Carvalho et al [14] and Arede et al [15] showed that early maturing basketball players performed better in physical tasks that required high levels of agility, endurance, power, and speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young players with early maturation often outperform their late maturing peers in muscle strength and endurance. While numerous studies exist on the effects of biological maturation on the physical and technical performance of adolescent basketball players [12,[15][16][17][18][19], there is a paucity of scientific literature on the assessment of anthropometric changes and performance characteristics in pre-adolescent basketballers.…”
Section: Introductionmentioning
confidence: 99%
“…The RAE exerted a greater impact on competitive contexts (men, post-adolescence group, U14-U18 categories) where the physical and anthropometric component has greater importance in the game [ 7 , 36 ]. Boys who reach puberty early tend to develop higher anthropometric values of height (approximately 20 cm) and vertical jump agility (approximately 12 cm) [ 84 ]. Therefore, statistics as decisive as the points scored or minutes played in a match clearly favour the type of players [ 85 ] who correspond, to a greater extent, to those born at the beginning of the year.…”
Section: Discussionmentioning
confidence: 99%